PERAN STRATEGIS LEMBAGA KEUANGAN SYARIAH BAGI UMKM DALAM MEWUJUDKAN PEMBANGUNAN EKONOMI - Muhdhori Ahmad (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2022)
Islamic financial institutions provide facilities that can be used by the community in the business sector to open up opportunities to build UMKM. UMKM are the main productive and competitive actors in the national economy. For this reason, the development of micro, small and medium enterprises needs to be the main priority of national economic development. This study aims to describe the role of Islamic financial institutions for UMKM in realizing economic development. This type of research is a literature review research with data sources obtained through a search on google schoolar with a number of predetermined variable keys. The results of this study include the role of financial institutions in the economy including the transfer of assets, transactions, liquidity and efficiency. Islamic financial institutions were established with the aim of promoting and developing the application of Islamic principles, sharia and their traditions into financial and banking transactions and related businesses. The role of Islamic financial institutions is to assist UMKM in developing their businesses so as to improve the economy of business people and indirectly have an impact on economic development.